PERBANDINGAN KOLOKASI DALAM NOVEL SALAH ASUHAN KARYA ABDOEL MOEIS DENGAN NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI - Ningrum, Retno Suprihaty; Charlina, Charlina; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to determine the collocation that used in Salah Asuhan novel by Abdoel Moeis with Negeri 5 Menara novel by Ahmad Fuadi which is classified into two kinds of collocation, they are antonym inclusive collocation and antonym exclusive collocation. The method in this research is analytical descriptive method with qualitative approach. In this research, writer use data technique accumulation by notation and documentation. The result that found in this research are inclusive collocation and exclusive collocation.Based on the research, writer found that both of two objects which are used by writer are indicate antonym inclusive collocation genre and the similarity of collation genre. The used of collocation between each novels are indicate the difference and similarity in using compatible words, and based on the research, the using of collocation between novel that accomplished by research object, has variation in using collocation genre.Key words: collocation antonym inclusive, collocation antonym exclusive, novel.